looking a trojan horse in the mouth: problematizing philosophy for/with children’s hope for social reform through the history of race and education in the us - wurtz, jonathan (childhood & philosophy, 2024)
Many P4/WC practitioners and theorists privilege the school as a space for thinking and practicing philosophy for/with children. Despite its coercive nature, thinkers such as Jana Mohr Lone, David Kennedy, and Nancy Vansieleghem argue that P4C is a Trojan horse intended to reform the education system from within. I argue, however, that the Trojan horse argument requires us to internalize an incomplete and historically decontextualized understanding of public schools that in turn can reify histories of white supremacy within our CPIs – a consequence that can be particularly harmful when practicing P4C with minority youth. To accurately adjudicate the value of public school classrooms for P4C – especially for those CPIs whose members are primarily Black, Latinx, Indigenous, or other youth of color — I contextualize the Trojan horse argument in the history of race and education in the United States. Through this historical analysis, I conclude that the reformist position becomes increasingly more untenable and that the material history of race and education in fact supports a pessimistic understanding of P4C in education. I end by reflecting on P4C’s need to rethink its privileging of schools as a primary site for philosophical inquiry and caution practitioners against using “social progress” as a justification for how and where they practice their craft. Instead, I encourage them to rethink how and where they practice P4C, based on the local historical and material conditions of the participants.